A comparison of the personality types of a group of adolescents as yielded by the Murphy-Meisgeier Vraelys vir Kinders and the Jung-Persoonlikheidsvraelys - Kritzinger,Anton Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1997.